A Study on Closed Halls in Traditional Dwellings in the Jiangnan Area, China. Issue 2 (1st May 2016) - Wang, Hui; Pu, Xincheng; Wang, Rongrong; Zeng, Yuting; Qi, Xiaofeng
Abstract: Halls in the traditional dwellings in northern China are generally closed, whereas those in the south are open. However, in the dwellings in Zhejiang and Jiangsu, many closed halls have partition doors that separate the indoor space from the yard. Focusing on the relationship between the hall and the yard, this study investigated the space of halls in Jiangnan (southern Jiangsu and northern Zhejiang) and its surrounding areas. A total of 89 cases in and 175 cases around Jiangnan were analyzed. Results indicated that the halls in the Jiangnan area are mostly closed, whereas those in the middle and south of Zhejiang, southeastern Anhui, eastern Jiangxi, and northern Fujian are mainly open. The closed halls in Jiangnan are relatively more special compared with those in its adjacent areas. Aside from the climate of hot-summers and cold-winters, the regional culture of preferring the quality of material life to orthodox etiquette is an important factor in the distinction. A closed hall provides comfort and privacy, thereby reducing the inner openness of the dwelling. These halls also lead to the emergence of assistant alleys in large dwellings.